Perinatal healthcare for women at risk of children’s social care involvement: a qualitative survey of professionals in England - Jenny Woodman; Claire Grant; Billie Lever Taylor; Claire Powell; Ruth Marion Blackburn; Rebecca Lacey; Tamsin Bicknell-Morel (BMJ Open, 2024)
Background Women with complex health needs are more at risk of having children’s social care involvement with their newborns than other mothers. Around the time of pregnancy, there are opportunities for health services to support women with these needs and mitigate the risk of mother–baby separation. Yet little is known about healthcare professionals’ experiences of providing this support.Methods We administered an online survey to perinatal healthcare professionals across England (n=70 responders), including midwives, obstetricians, perinatal psychologists/psychiatrists and health visitors. We asked about their experiences of providing care for pregnant women with chronic physical conditions, mental health needs, intellectual/developmental disabilities and substance use disorders, who might be at risk of children’s social care involvement. We conducted a framework analysis.Results We constructed five themes from participant data. These include (1) inaccessible healthcare for women with complex needs, (2) the challenges and importance of restoring trust, (3) services focusing on individuals, not families, (4) the necessity and caution around multidisciplinary support and (5) underfunded services inhibiting good practice.Conclusions Women who are at risk of children’s social care involvement will likely experience perinatal healthcare inequities. Our findings suggest that current perinatal healthcare provision for this population is inadequate and national guidelines need updated to inform support.